(untitled) (Coordinates of Public Administration, 2026)
The article provides a comprehensive analysis of the transformation of international information cooperation in the context of intensifying global geopolitical competition and the emergence of new digital threats. The transition from classical concepts of «soft power» to cognitive warfare strategies is studied, where the main target of destructive influence is the human mind, mechanisms of perception of reality and decision-making. It is substantiated that the modern information space has turned into the «fifth domain» of military operations, where the boundary between peace and conflict has virtually disappeared. Particular attention is paid to the symbiosis of psychological pressure and technical cyber threats implemented by state aggressor actors through manipulation of algorithms, the use of generative artificial intelligence to create deepfakes and conduct large-scale financial special operations. The risks associated with the era of quantum computing, which threatens existing encryption systems, as well as the phenomenon of «digital colonialism», through which authoritarian regimes export the ideology of control under the guise of technological infrastructure, are analyzed. A key element of the work is the generalization of the unique experience of Ukraine as a training ground for hybrid confrontations. The effectiveness of the «state in the cloud» model and network defense (cooperation between the state, the private IT sector and volunteers) is highlighted, demonstrating new approaches to ensuring national resilience. It is proven that traditional hierarchical security structures are insufficient, therefore the future architecture of the international order should be based on «webs of trust», automated detection of manipulations, the implementation of post-quantum cryptography standards and the establishment of strict legal liability (attribution) for cybercrimes.